Characteristics and Abundance of Microplastics in the Feces of Communities on the Banks of the Musi River, Palembang - Anwar, Khairil; Damiri, Nurhayati; Windusari, Yuanita; Zulkarnain, Mohammad (Tropical Health and Medical Research, 2025)
Microplastic pollution has become an increasingly worrying global environmental issue. Microplastics are plastic particles measuring less than 5 mm from the degradation of large plastics or using products containing microplastics. Microplastics can enter the human body through contaminated food, water, and air, with feces being one of the indicators of exposure. This study aims to analyze the characteristics and abundance of microplastics in feces in communities on the banks of the Musi River in Palembang City. This study used a descriptive design with laboratory analysis. Fecal samples were collected from 50 respondents selected by purposive sampling based on fish consumption patterns and water sourced from the Musi River. The study was carried out using the microplastic separation method using a solution and particle identification using a stereo microscope and FTIR spectroscopy. The results showed that microplastics were found in all respondents' feces samples, with concentrations ranging from 9-27 particles per gram and an average of 18 particles per gram. The dominant types of microplastic polymers found were Polystyrene (PS), Nylon, Polyvinyl chloride (PVC), Polypropylene (PP), Polyethylene Terephthalate (PET), and Polyethylene (PE). It was concluded that the presence of microplastics in feces indicates significant exposure. Microplastics, such as fragments, fibers, and other particles, were found in people's feces with various shapes, sizes, and colors. The abundance of microplastics in feces indicates contamination, which most likely comes from consuming food and drinks exposed to microplastics. It is recommended that a campaign be carried out to reduce single-use plastic or increase waste processing in riverbank areas.